2019
DOI: 10.1101/2019.12.29.890608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking niche change through time: simultaneous inference of ecological niche evolution and estimation of contemporary niches

Abstract: The environmental niche of a species is often studied from two different perspectives. Niche modelling correlates a species’ niche to known observations from contemporary species distribution. Niche evolution applies phylogenetic methods on summary statistics of species distribution to infer the patterns of changing niche over time. Even though the two areas of research are fundamentally linked and are typically both based on the same species distribution data, modelling the contemporary niche and inferring ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…But we can improve our prediction of species tolerance to environmental stress if we incorporate evolutionary history into our SDMs. Incorporating phylogeny into SDMs allows us to model the impact of evolutionary processes on current distribution and leads to better prediction of salt-tolerant species (Hua, Cardillo, & Bromham, 2019).…”
Section: Filling In the Gaps: Macroecological Predictions Of Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…But we can improve our prediction of species tolerance to environmental stress if we incorporate evolutionary history into our SDMs. Incorporating phylogeny into SDMs allows us to model the impact of evolutionary processes on current distribution and leads to better prediction of salt-tolerant species (Hua, Cardillo, & Bromham, 2019).…”
Section: Filling In the Gaps: Macroecological Predictions Of Stressmentioning
confidence: 99%
“…We have applied this approach to studying the evolution of salt tolerance in Australian Acacia species (Hua et al, 2019). The approach not only better predicts known Acacia halophytes than using SDMs alone, but also paints a picture of the history of salt tolerance in Australian Acacia species over time and space.…”
Section: Filling In the Gaps: Macroecological Predictions Of Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we infer the history of adaptation to extreme environments by applying a recently developed method, the Niche Evolution Model (NEMo), that combines Environmental Niche Modelling (ENM) and reconstruction of the evolutionary history of fundamental niche in a single statistical framework (Hua et al 2021). This method uses species distribution data to characterise the realised niches of each contemporary species at the tips of a phylogeny, and reconstructs evolution of the fundamental niche and the associated changes in the realised niche by modelling key driving processes: (1) shift in areas of tolerable conditions and adaptation of lineages to changing conditions (hereafter referred to as an "adaptation event"); (2) dispersal away from areas that are no longer suitable and into accessible areas of suitable habitat; (3) speciation and divergence along lineages' environmental tolerances (hereafter "speciation event").…”
Section: Introductionmentioning
confidence: 99%
“…2015; Hua et al. 2019). However, in direct contrast, other studies have found no evidence for a relationship between climatic conditions and climatic niche changes (e.g., Schnitzler et al.…”
mentioning
confidence: 99%